Scientific argumentation and the promotion of conceptual changes - Heng, Lee Ling (Serials Publications, 2016)
Argumentative practices are central to science education due to their ability to foster students' understanding of scientific concepts, and to eliminate alternative frameworks. In addition, conceptual changes are likely to occur when deeper cognitive processing is required, especially when students are asked to clarify, explain, and defend their own ideas. Thus, this study aims to examine conceptual changes in the context of scientific argumentation, based on the triplet relationship in chemistry. Students are first asked to answer an Open-ended Scientific Argumentation Test 1 (OSAT 1). Based on the arguments constructed, 32 students are selected using purposive sampling to complete the OSAT 2 in a guided group argumentation setting. Discussions during the guided group argumentations are also recorded. Data are then analysed using content analysis technique to identify the process of conceptual changes. The findings of this study show that almost all of the students change their existing alternative frameworks to the correct scientific concepts after being involved in a guided group argumentation process. This study also shows that the process of deep thinking between two alternative concepts leads to conceptual changes, which helps students in constructing complex arguments that linked between the macroscopic, sub-microscopic, and symbolic levels of the triplet relationship. Hence, the teaching and learning of science need to emphasize on guided group argumentations to eliminate alternative frameworks and to promote conceptual changes.